Revenue implications of trade liberalization - Ebrill, Liam P.; Gropp, Reint 1966-; Stotsky, Janet G. (International Monetary Fund, 1999)
The apparent contradiction between trade liberalization and continuing high trade tax revenue raises the important question of how, precisely, the one affects the other. Although policymakers generally recognize the long-term benefits of trade liberalization, some have argued for at least a slower pace, in part because of revenue concerns. This paper seeks to address these issues in three complimentary ways: through an overview of the factors that may have a bearing on the question, through a review of trends in trade tax revenue both globally and in selected countries, and through econometric analysis
Keywords: Free trade; Econometric models; International trade; Revenue